Genetic relatedness between Japanese and European isolates of Clostridium difficile originating from piglets and their risk associated with human health - Usui, Masaru; Nanbu, Yukie; Oka, Kentaro; Takahashi, Motomichi; Inamatsu, Takashi; Asai, Tetsuo; Kamiya, Shigeru; Tamura, Yutaka (Frontiers in Microbiology, 2014)
Clostridium difficile colonization in pig intestine has been a public health concern. We analyzed C. difficile prevalence among piglets in Japan to clarify their origin and extent of the associated risk by using molecular and microbiological methods for both swine and human clinical isolates and foreign isolates. C. difficile was isolated from 120 neonatal piglet faecal samples. Toxin gene profile, antimicrobial susceptibilities, PCR ribotype, and multiple-locus variable-number tandem-repeat analysis (MLVA) type of swine isolates were determined and compared with those of human clinical and foreign isolates. One-hundred C. difficile strains were isolated from 69 (57.5%) samples, and 61 isolates (61%) were toxin gene-positive. Some isolates were resistant to antimicrobials, contributing to antibiotic-associated diarrhoea by C. difficile. These results suggest that C. difficile, prevalent among Japanese pigs, is a potential risk for antibiotic-associated diarrhoea. Furthermore, PCR ribotype 078 (12 isolates), which has been linked to multiple outbreaks worldwide, was the third-most frequently isolated of the 14 PCR ribotypes identified. Moreover, MLVA revealed that all 12 PCR ribotype 078 isolates were genetically related to European PCR ribotype 078 strains found in both humans and pigs. To date, in Japan, many breeding pigs have been imported from European countries. The genetic relatedness of C. difficile isolates of Japanese swine origin to those of European origin suggests that they were introduced into Japan via imported pigs.